Potentiating the Antitumor Activity of Cytotoxic T Cells via the Transmembrane Domain of IGSF4 That Increases TCR Avidity - Kim, Hye-Ran; Park, Jeong-Su; Fatima, Yasmin; Kausar, Maiza; Park, Jin-Hwa; Jun, Chang-Duk (Frontiers in Immunology, 2021)
A robust T-cell response is an important component of sustained antitumor immunity. In this respect, the avidity of TCR in the antigen-targeting of tumors is crucial for the quality of the T-cell response. This study reports that the transmembrane (TM) domain of immunoglobulin superfamily member 4 (IGSF4) binds to the TM of the CD3 ζ-chain through an interaction between His177 and Asp36, which results in IGSF4-CD3 ζ dimers. IGSF4 also forms homo-dimers through the GxxVA motif in the TM domain, thereby constituting large TCR clusters. Overexpression of IGSF4 lacking the extracellular (IG4ΔEXT) domain potentiates the OTI CD8+ T cells to release IFN-γ and TNF-α and to kill OVA+-B16F10 melanoma cells. In animal models, IG4ΔEXT significantly reduces B16F10 tumor metastasis as well as tumor growth. Collectively, the results indicate that the TM domain of IGSF4 can regulate TCR avidity, and they further demonstrate that TCR avidity regulation is critical for improving the antitumor activity of cytotoxic T cells.